Anti-dandruff, itching-relieving and softening shampoo composition

By modifying fatty alcohol polyoxyethylene ether by photoelectric means, a new surfactant with both anionic and nonionic dual properties was prepared, and combined with other surfactants, solving the irritation problem of existing shampoos on the scalp and hair, and preparing shampoos that are efficient in removing stains, smoothing hair care and anti-itchi.

CN119587410APending Publication Date: 2025-03-11王勤
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411782991.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

While removing stains, existing shampoos may cause irritation to the scalp and hair, resulting in increased dandruff, itching scalp and hair damage.

Method used

By modifying fatty alcohol polyoxyethylene ether by photoelectric means, a new surfactant with anionic and nonionic dual properties was obtained, and combined with anionic surfactant and nonionic surfactant to prepare a shampoo with high foaming ability and wetting effect.

Benefits of technology

The prepared shampoo foam is rich and delicate, has moderate detergent ability, is easy to rinse, and has no irritation to hair, skin, and eyes. The washed hair is shiny, smooth, elastic, and has anti-it-it-out effects, achieving the effect of removing dandruff and anti-it-it-it-balanced scalp oil secretion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
Patent Text Reader

Abstract

The anti-dandruff, itching-relieving and softening shampoo composition provided by the invention is rich and fine in foam, moderate in detergency, easy to rinse and non-irritant to hair, skin and eyes, the washed hair is bright, soft and elastic, and good in dry and wet combing property, a user particularly feels cool, refreshing and comfortable, and the anti-dandruff, itching-relieving and scalp grease secretion balancing effects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the category of daily cosmetics and relates to an anti-dandruff, anti-itching and smoothing shampoo composition. Background Art

[0002] Shampoo has a long history of development. The emergence of conditioner has changed people's shampooing habits. People no longer focus on hair cleanliness alone, but use conditioner with hair to focus on hair smoothness. Conditioner needs to be used after shampooing, and it is not easy to rinse out. It needs to be rinsed many times, wasting time and resources. Although ordinary shampoo has a strong degreasing power and effectively removes dirt, its strong degreasing power will irritate the scalp and hair while removing dirt, causing side effects such as hair damage, scalp itching and increased dandruff. Therefore, adding hair care ingredients to ordinary shampoo can not only remove dirt but also reduce such damage, maintain hair, and improve the combing properties of hair in dry and wet states.

[0003] Surfactants are a large class of organic compounds that were discovered earlier. They are substances that can significantly reduce surface tension when used in small amounts. Surfactant molecules are composed of non-polar lipophilic hydrocarbon chains and polar hydrophilic groups. These two parts are located at the two ends of the molecule, forming a symmetrical or asymmetrical structure. Due to the existence of this structure, when the concentration of surfactant molecules is low, the molecules can spontaneously adsorb to the air (or liquid) interface, extending the hydrocarbon chains out of the water phase to reduce free energy. When the surfactant molecules reach the critical micelle concentration, the surfactant molecules adsorbed on the air (or liquid) interface have reached saturation, and the solute molecules in the water phase contact each other through diffusion and then aggregate, forming a molecular ordered aggregate with a "shell-core" structure in which the hydrocarbon chains are wrapped inside and the hydrophilic groups form the outer shell. The formation of this aggregate is also conducive to reducing the free energy of the system, thereby reducing the surface tension of water and increasing the solubility of organic compounds.

[0004] Surfactants can be divided into four categories based on the nature of their molecular charge, namely anionic, cationic, nonionic and amphoteric surfactants. Anionic surfactants: surfactants with negatively charged parts that play a role in surface activity after ionization in water; Cationic surfactants: surfactants with positively charged hydrophilic groups connected to lipophilic groups after the molecules are dissolved in water and ionized. Cationic surfactants are divided into three categories: amine salts, quaternary ammonium salts and heterocyclic rings according to the position of nitrogen atoms in their molecules. Amine salt surfactants have low solubility in water, are relatively stable in acidic media, and are easily hydrolyzed in neutral and alkaline media; Nonionic surfactants: surfactants that do not produce ions in aqueous solutions, and their hydrophilic groups are mainly composed of a certain number of oxygen-containing groups, such as hydroxyl groups and polyoxyethylene chains. Amphoteric surfactants: surfactants with both anionic and cationic properties. From its structure, there are both cations and anions connected to the hydrophobic groups. Nonionic and anionic surfactants are superior to other types of surfactants in terms of variety and output, so these two types of surfactants account for more than 80% of all surfactants.

[0005] Fatty alcohol ether carboxylates are a type of alkyl ether carboxylate surfactants, which mainly include alcohol ether carboxylates (AEC), phenol ether carboxylates (APEC) and alkanolamide ether carboxylates (AMEC).

[0006] Fatty alcohol ether carboxylates (AEC) are the main varieties of surfactant industry development. They are a kind of multifunctional green surfactants with dual characteristics of nonionic and anionic surfactants. Structurally, it is a polyoxyethylene (EO) with a certain adduct number embedded between the hydrophilic and hydrophobic groups of soap. The introduction of EO chain makes AEC have better water solubility, calcium soap dispersibility and hard water resistance than soap. Moreover, products with different characteristics can be prepared by adjusting the length of the hydrophobic chain, the adduct number of EO and pH. In addition, it has good compatibility and can be compounded with other types of surfactants. It has excellent emulsification performance for oils and fats, and strong anti-graying ability, and is widely used. And it has attracted widespread attention for its advantages such as temperature stability, excellent anti-decomposition ability, mildness, pollution-free, easy biodegradability and safety. As a detergent, dispersant, wetting agent, foaming agent, mildness improver, crude oil demulsifier, heavy oil viscosity reducer, sewage treatment agent, antistatic agent, emulsifier, softener, etc., it is used in cosmetics, textiles, petroleum, biochemistry, pharmaceuticals, food processing and other fields. It is widely used in daily chemical products, personal care, food, textiles, machinery and electronics, etc. along with alkyl polyglycosides and alcohol ether phosphate monoesters, and is one of the surfactant products.

[0007] The synthesis method of fatty alcohol ether carboxylate includes: carboxymethylation method, oxidation method, nitroxide free radical catalytic oxidation method, acrylonitrile addition or electrochemical method, electrochemical method: CN105568310B provides an electrochemical synthesis method of fatty alcohol polyoxyethylene ether carboxylic acid or its salt, characterized in that it includes the following steps: the first step: dissolving fatty alcohol polyoxyethylene ether in a buffer solution, adding a catalyst, and preparing a micro-nano emulsion; the second step: inserting a pair of platinum electrodes as an anode and a cathode into the micro-nano emulsion, passing a constant current, and stirring electrolysis at room temperature; the third step: after the electrolysis is completed, the reaction solution is extracted with ethyl acetate to remove the catalyst, separated, and a hydrogen-type cation exchange resin is added to the aqueous solution layer for ion exchange to obtain an aqueous phase solution of fatty alcohol ether carboxylate or fatty alcohol ether carboxylic acid, filtering to remove the resin, and concentrating to obtain fatty alcohol polyoxyethylene ether carboxylic acid or its salt. The reaction of the present invention is carried out in the aqueous phase, without using an organic solvent, using oxygen in the air as an oxidant, the catalyst is low in toxicity, and the reaction temperature is room temperature; the reaction has no by-products, and the atom economy is 100%. Summary of the invention

[0008] The present invention provides an anti-dandruff, anti-itching and smooth shampoo composition, which has a simple preparation process and readily available raw materials. It is the first time to propose a novel surfactant having both anionic and nonionic properties obtained by modifying fatty alcohol polyoxyethylene ether by photoelectric means, wherein the novel surfactant is obtained by vacuum distilling an electrolyte product, and then the novel surfactant is compounded with anionic surfactant and nonionic surfactant to obtain a key component of a shampoo having high-efficiency foaming ability and wetting effect. Then, by adding other auxiliary ingredients, such as anti-dandruff agents, flavor preparations, etc., the obtained shampoo has rich and delicate foam, moderate detergency, easy rinsing, and no irritation to hair, skin, and eyes. The washed hair is bright, smooth, elastic, and has good dry and wet combing properties, and is particularly cool and refreshing, and has anti-itching effect, achieving the effects of anti-dandruff, anti-itching, and balancing scalp oil secretion.

[0009] Specifically: An anti-dandruff, anti-itching and smoothing shampoo composition, comprising the following ingredients: Fatty alcohol polyoxyethylene ether carboxylic acid or sodium fatty alcohol polyoxyethylene ether carboxylate 22.5 wt.%; IgeponA 6 13wt.%; Alkyl polyglycosides 8wt.%; Ethylene glycol distearate 1 wt.%; Coconut oil monoethanolamide 1 wt.%; Pyrithione salt 1.5wt.%; Preservatives 0.01 wt. %; Fragrance 0.02 wt.%; Antioxidant 0.02 wt.%; Deionized water was added to 100.00; Citric acid adjusts pH to 5.5-6.2.

[0010] The viscosity of the shampoo is 6-10Pa . S.

[0011] The fatty alcohol polyoxyethylene ether carboxylic acid or the corresponding salt is obtained by photoelectric modification, and the process is as follows: (1) Preparation of photoanode: (a) Titanium sheet pretreatment: After mechanical polishing, the titanium sheet was ultrasonically cleaned with acetone, ethanol and deionized water in sequence to obtain a smooth titanium sheet substrate; (b) Anodic oxidation to obtain nanoarrays: The surface-treated titanium sheet is used as the anode and the platinum sheet is used as the cathode, and the two are placed in an anodic oxidation electrolyte. The composition of the anodic oxidation electrolyte is as follows: 0.25 wt.% ammonium fluoride, 95 vol.% ethanol aqueous solution and 5 vol.% Deionized water, appropriate amount of sulfuric acid to adjust pH = 5.8, anodize at 50V constant voltage for 2 hours at 25°C, and rinse with deionized water after anodization; (c) Loading photoelectroactive catalyst: 1.5 g of bismuth nitrate was dissolved in a mixed solution of 30 mL of propylene glycol and 24 mL of ethanol, and the mixture was stirred for 1 h until it was uniformly mixed. The titanium sheet treated in step (b) and the mixed solution were transferred into a reactor and reacted at 180° C. for 12 h, cooled naturally to room temperature, and then placed in a muffle furnace and heated to 350° C. at a heating rate of 5° C. / min and calcined for 1 h, and cooled naturally to room temperature; (d) Loading precious metal catalysts: The material prepared in step (c) is impregnated in a solution of chloroplatinic acid by an equal volume impregnation method and dried in an inert atmosphere. The photoanode finally obtained is 3 wt.% Pt / titanic bismuth acid / titanium oxide / titanium.

[0012] (2) Preparation of alcohol ether carboxylates by electrochemical modification: 3wt.% Pt / titanic bismuth acid / titanium oxide / titanium photoanode and platinum cathode are respectively inserted into an electrolytic cell solution, wherein the electrolyte solution is an emulsion composed of 15-20g fatty alcohol polyoxyethylene ether, 1-1.5g sodium chloride, and 500-750mL deionized water. A DC voltage is used with a voltage intensity of 20-30V, a xenon lamp is used as the light source, and the light intensity of the light is 15-30mW / cm 2 , temperature is 25-35°C, stirring speed is 150-200rpm, time is 10-12h; (3) Concentrate by vacuum distillation to obtain the modified surfactant.

[0013] The specific preparation process of shampoo is as follows: (a) adding a certain amount of deionized water and the modified surfactant obtained by vacuum distillation concentration into a reaction vessel, and stirring at 200-250 rpm for 5-7 minutes at 40-45°C; (b) continuing to add Igepon A and alkyl polyglycoside, stirring at 200-250 rpm for 10-15 min at 40-45° C. to obtain a homogenized emulsion; (c) after cooling to 30-35° C., adding ethylene glycol distearate and coconut oil monoethanolamide, and stirring at 200-250 rpm for 3-5 minutes; (d) Continue to add pyrithione salt, preservative, fragrance, antioxidant and deionized water, and use citric acid to adjust the pH, continue stirring for 10-15 minutes, cool to room temperature, and obtain the desired shampoo.

[0014] A method for preparing a highly effective repairing and anti-dandruff shampoo, the shampoo comprising at least a novel surfactant having both anionic and nonionic properties obtained by photoelectrochemical modification, the anionic surfactant and the nonionic surfactant, the novel surfactant having both anionic and nonionic properties accounting for 15.0% to 30% of the weight of the composition; the anionic surfactant accounting for 12% to 14% of the weight of the composition; and the nonionic surfactant accounting for 7% to 9% of the weight of the composition.

[0015] Furthermore, the novel surfactant having both anionic and nonionic properties is preferably an alcohol ether carboxylate, such as fatty alcohol polyoxyethylene ether carboxylic acid or its salt.

[0016] Furthermore, the anionic surfactant is a sulfonalkyl ester of a fatty acid, such as IgeponA, or a sulfonalkyl amide of a fatty acid, such as IgeponT.

[0017] The nonionic surfactant is selected from alkanolamide nonionic surfactants, such as fatty acid diethanolamide or alkyl polyglycoside.

[0018] The invention also comprises an anti-dandruff agent, which is a pyridinethione salt and is used in an amount of 1-2 wt.%.

[0019] The present invention prepares the photoanode in advance, takes the titanium sheet as the substrate, and the surface of the titanium sheet after surface pretreatment is smooth and clean, and then performs anodization in ammonium fluoride and ethanol aqueous solution to obtain the nanoarray as shown in the attached Figure 1As shown in (a), TiO2 is one of the most widely studied semiconductor materials. It has the advantages of low cost, non-toxicity, good thermal stability, and high photoelectrocatalytic activity. Then, a bismuth titanate layer is formed on the surface of the nanoarray by hydrothermal means. The overall morphology is uniform. Due to the increase in visible light absorption by bismuth titanate and the semiconductor heterojunction formed with TiO2, the oxidation effect of the photoanode is significantly improved. Then, the noble metal catalyst is loaded on the surface of titanium / titanium oxide / bismuth titanate by an equal volume impregnation method. Its morphology is shown in the attached figure. Figure 1 As shown in (b), a DC voltage is provided on the electrode surface to further improve the electrode oxidation effect. Compared with the prior art, (1) the photoanode of the present invention does not need to apply oxygen to oxidize the electrolyte. Under the action of light source and DC power, the oxidation performance of the electrode of the present invention is significantly improved, and no additional oxygen oxidation is required; (2) the catalyst does not need to be separated from the electrolyte for a second time. The surface area of ​​the substrate after surface anodization and hydrothermal treatment is large. The precious metal with reduced loading will be completely adsorbed on the surface of the nanoarray, evenly distributed, without agglomeration, and will not enter the electrolyte during the electrolysis process to cause electrolyte pollution, so no secondary separation is required.

[0020] The present invention uses fatty alcohol polyoxyethylene ether as a raw material and prepares a new surfactant through photoelectric modification. The surfactant is a mixture. The electrolysis product includes but is not limited to fatty alcohol polyoxyethylene ether non-ionic surfactant, dual-functional fatty alcohol polyoxyethylene ether carboxylic acid or corresponding salt, and sodium chloride, wherein the dual-functional fatty alcohol polyoxyethylene ether carboxylic acid or corresponding salt is the main component. In addition, it should be noted that the electrolyte of the present invention can be used as a surfactant product and directly used in the preparation of shampoo after only undergoing reduced pressure distillation.

[0021] The raw material of the present invention is fatty alcohol polyoxyethylene ether, which is one of the main varieties of polyoxyethylene nonionic surfactants, and has the advantages of strong permeability, high detergency, good compatibility, rapid dissolution, etc., but it has strong degreasing power for skin and hair, great irritation to skin, and weak foaming power; it has poor water solubility and hard water resistance, and its application as a shampoo raw material is subject to certain restrictions, so it needs to be modified. As described in the background technology part, the preparation method is relatively complicated, or separation is difficult. In comparison, the present invention does not require complicated post-treatment, the electrolytic treatment process is simple, the conversion rate is high, and the cost performance is high. Specifically, the fatty alcohol polyoxyethylene ether is oxidized into fatty alcohol polyoxyethylene ether carboxylic acid through photoelectric oxidation. As for the mechanism of improving the conversion rate of fatty alcohol polyoxyethylene ether carboxylic acid product by photoelectric oxidation, it remains to be studied.

[0022] Beneficial technical effects: (1) The present invention modifies and processes fatty alcohol polyoxyethylene ether by electrochemical and light source coupling to obtain a high-performance fatty alcohol polyoxyethylene ether carboxylic acid or salt mixture electrolyte, with a high product conversion rate, no need for additional oxygen oxidation during the reaction process, and no need for complex post-treatment of the corresponding product, which is significantly better than the prior art. (2) The above-mentioned fatty alcohol polyoxyethylene ether carboxylic acid or salt mixture electrolyte product is subjected to reduced pressure distillation, and then the new surfactant is compounded with anionic surfactants and non-ionic surfactants to obtain a key component of shampoo with high foaming ability and wetting effect. (3) The prepared shampoo has rich and delicate foam, moderate detergency, easy rinsing, and no irritation to hair, skin, and eyes. The washed hair is shiny, soft, elastic, and has good dry and wet combing properties. It feels especially cool and refreshing, and has an antipruritic effect, achieving the effects of antidandruff and antipruritic, and balancing the oil secretion of the scalp. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Attached Figure 1 Topography of the photoanode of the present invention.

[0024] Attached Figure 2 Combability test graph of Examples 5-6 of the present invention. DETAILED DESCRIPTION Example 1

[0025] A method for preparing a surfactant, wherein the main component of the surfactant is fatty alcohol polyoxyethylene ether carboxylic acid or its corresponding salt, and the corresponding preparation method is as follows: (1) Preparation of photoanode: (a) Titanium sheet pretreatment: After mechanical polishing, the titanium sheet was ultrasonically cleaned with acetone, ethanol and deionized water in sequence to obtain a smooth titanium sheet substrate; (b) Anodic oxidation to obtain nanoarrays: The surface-treated titanium sheet is used as the anode and the platinum sheet is used as the cathode. The two sheets are placed in an anodic oxidation electrolyte. The composition of the anodic oxidation electrolyte is as follows: 0.25 wt.% ammonium fluoride, 95 vol.% ethanol aqueous solution, and an appropriate amount of sulfuric acid to adjust the pH to 5.8. The anodic oxidation is carried out at a constant voltage of 50 V for 2 hours at a temperature of 25°C. After the anodic oxidation, the anodic oxidation is washed with deionized water. (c) Loading photoelectroactive catalyst: 1.5 g of bismuth nitrate was dissolved in a mixed solution of 30 mL of propylene glycol and 24 mL of ethanol, and the mixture was stirred for 1 h until it was uniformly mixed. The titanium sheet treated in step (b) and the mixed solution were transferred into a reactor and reacted at 180° C. for 12 h, cooled naturally to room temperature, and then placed in a muffle furnace and heated to 350° C. at a heating rate of 5° C. / min and calcined for 1 h, and cooled naturally to room temperature; (d) Loading precious metal catalysts: The material prepared in step (c) is impregnated in a solution of chloroplatinic acid by an equal volume impregnation method and dried in an inert atmosphere. The photoanode finally obtained is 3 wt.% Pt / titanic bismuth acid / titanium oxide / titanium.

[0026] (2) Electrochemical modification to prepare alcohol ether carboxylates: 3 wt.% Pt / titanic bismuth acid / titanium oxide / titanium photoanode and platinum cathode were respectively inserted into an electrolytic cell solution, wherein the electrolyte solution was an emulsion composed of 17.5 g fatty alcohol polyoxyethylene ether, 1.25 g sodium chloride, and 625 mL deionized water. A DC voltage was used with a voltage intensity of 25 V, a xenon lamp was used as the light source, and the light intensity was 25 mW / cm 2 , temperature is 30°C, stirring speed is 200rpm, time is 11h; (3) Concentrate by vacuum distillation to obtain the modified surfactant. Example 2

[0027] A method for preparing a surfactant, wherein the main component of the surfactant is fatty alcohol polyoxyethylene ether carboxylic acid or its corresponding salt, and the corresponding preparation method is as follows: (1) Preparation of photoanode: (a) Titanium sheet pretreatment: After mechanical polishing, the titanium sheet was ultrasonically cleaned with acetone, ethanol and deionized water in sequence to obtain a smooth titanium sheet substrate; (b) Anodic oxidation to obtain nanoarrays: The surface-treated titanium sheet is used as the anode and the platinum sheet is used as the cathode. The two sheets are placed in an anodic oxidation electrolyte. The composition of the anodic oxidation electrolyte is as follows: 0.25 wt.% ammonium fluoride, 95 vol.% ethanol aqueous solution, and an appropriate amount of sulfuric acid to adjust the pH to 5.8. The anodic oxidation is carried out at a constant voltage of 50 V for 2 hours at a temperature of 25°C. After the anodic oxidation, the anodic oxidation is washed with deionized water. (c) Loading precious metal catalysts: The material prepared in step (c) is impregnated in a solution of chloroplatinic acid by an equal volume impregnation method and dried in an inert atmosphere. The photoanode finally obtained is 3 wt.% Pt / titanic bismuth acid / titanium oxide / titanium.

[0028] (2) Preparation of alcohol ether carboxylates by electrochemical modification: 3 wt.% Pt / titanic bismuth acid / titanium oxide / titanium photoanode and platinum cathode were respectively inserted into an electrolytic cell solution, wherein the electrolyte solution was an emulsion consisting of 17.5 g fatty alcohol polyoxyethylene ether, 1.25 g sodium chloride, and 625 mL deionized water, using a DC voltage, a temperature of 30 °C, a stirring speed of 200 rpm, and a time of 11 h; (3) Concentrate by vacuum distillation to obtain the modified surfactant.

[0029] Example 2 can be briefly described as removing the titanium oxide / bismuth titanate heterojunction and light source of the photoanode, and mainly relying on the anode and the catalyst platinum metal to catalyze the oxidation of fatty alcohol polyoxyethylene ether. Example 3

[0030] A surfactant composition: Surfactant product obtained from Example 1: 5.625 wt.%; IgeponA 3.25wt.%; Alkyl polyglycosides 2wt.%; The balance is deionized water. Example 4

[0031] A surfactant composition: Surfactant product obtained from Example 2: 5.625 wt.%; IgeponA 3.25wt.%; Alkyl polyglycosides 2wt.%; The balance is deionized water.

[0032] The surfactant composition prepared in Examples 3-4 was formulated into a stable solution, left for 24 hours, and its surface performance parameters were tested: The surface activity of the fatty alcohol polyoxyethylene ether carboxylic acid or sodium prepared in Example 1 was tested, and the corresponding cmc , minimum surface tension γ cmc、 Saturated adsorption capacity Γ max and minimum occupied area A min They are 117.23 mg / L, 32.78 mN / m, and 1.49 μmol / m 2 , 1.13nm 2 .

[0033] ρ corresponding to Example 2 cmc , minimum surface tension γ cmc、 Saturated adsorption capacity Γ max and minimum occupied area A min They are 298.7 mg / L, 28.46 mN / m, and 1.44 μmol / m 2 , 1.18nm 2 .

[0034] Example 3 corresponding to ρ cmc , minimum surface tension γ cmc、 Saturated adsorption capacity Γ max and minimum occupied area A min They are 22.41 mg / L, 29.15 mN / m, and 2.13 μmol / m 2 、0.76nm 2.

[0035] Example 4 corresponding to ρ cmc , minimum surface tension γ cmc、 Saturated adsorption capacity Γ max and minimum occupied area A min They are 20.18 mg / L, 31.01 mN / m, and 1.85 μmol / m 2 、0.90nm 2 .

[0036] From the above parameters, it can be seen that the surfactant prepared in Example 1 is significantly better than that in Example 2, among which Example 3 has the largest saturated adsorption capacity and the smallest cross-sectional area occupied by the polar head group, that is, the corresponding surface activity is the strongest, and its effect is better than that of Example 4. Example 5

[0037] The corresponding shampoo was prepared using the surfactant prepared in Example 1: Fatty alcohol polyoxyethylene ether carboxylic acid or sodium fatty alcohol polyoxyethylene ether carboxylate 22.5 wt.%; IgeponA 13wt.%; Alkyl polyglycosides 8wt.%; Ethylene glycol distearate 1 wt.%; Coconut oil monoethanolamide 1 wt.%; Pyrithione salt 1.5wt.%; Preservatives 0.01 wt. %; Fragrance 0.02 wt.%; Antioxidant 0.02 wt.%; Deionized water was added to 100.00; The pH was adjusted to 6.0 ± 0.2 with citric acid. Example 6

[0038] The corresponding shampoo was prepared using the surfactant prepared in Example 2: Fatty alcohol polyoxyethylene ether carboxylic acid or sodium fatty alcohol polyoxyethylene ether carboxylate 22.5 wt.%; IgeponA 13wt.%; Alkyl polyglycosides 8wt.%; Ethylene glycol distearate 1 wt.%; Coconut oil monoethanolamide 1 wt.%; Pyrithione salt 1.5wt.%; Preservatives 0.01 wt. %; Fragrance 0.02 wt.%; Antioxidant 0.02 wt.%; Deionized water was added to 100.00; The pH was adjusted to 6.0 ± 0.2 with citric acid.

[0039] The shampoo of Example 5-6 is subjected to combing test, see attached Figure 2 The dynamic friction coefficient of Example 5 is about 0.122, and the dynamic friction coefficient of Example 6 is about 0.142. The test results show that the shampoo prepared in Example 5 of the present invention has better hair care and conditioning performance.

[0040] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A shampoo composition for removing dandruff, relieving itching and softening hair, characterized in that Including composition: Fatty alcohol polyoxyethylene ether carboxylic acid or sodium fatty alcohol polyoxyethylene ether carboxylate 22.5 wt.%; IgeponA 13wt.%; Alkyl polyglycosides 8wt.%; Ethylene glycol distearate 1 wt.%; Coconut oil monoethanolamide 1 wt.%; Pyrithione salt 1.5wt.%; Preservatives 0.01 wt. %; Fragrance 0.02 wt.%; Antioxidant 0.02 wt.%; Add deionized water to 100.00; Citric acid adjusts pH to 5.5-6.

2.

2. The anti-dandruff, anti-itching and smoothing shampoo composition according to claim 1, characterized in that The fatty alcohol polyoxyethylene ether carboxylic acid or the sodium fatty alcohol polyoxyethylene ether carboxylate is obtained by photoelectric modification, and the treatment process is as follows: (1) Preparation of photoanode: (a) Titanium sheet pretreatment: After mechanical polishing, the titanium sheet was ultrasonically cleaned with acetone, ethanol and deionized water in sequence to obtain a smooth titanium sheet substrate; (b) Anodic oxidation to obtain nanoarrays: The surface-treated titanium sheet is used as the anode and the platinum sheet is used as the cathode, and the two are placed in an anodic oxidation electrolyte. The composition of the anodic oxidation electrolyte is as follows: 0.25 wt.% ammonium fluoride, 95 vol.% ethanol aqueous solution and 5 vol.% Deionized water, appropriate amount of sulfuric acid to adjust pH = 5.8, anodize at 50V constant voltage for 2 hours at 25°C, and rinse with deionized water after anodization; (c) Loading photoelectroactive catalyst: 1.5 g of bismuth nitrate was dissolved in a mixed solution of 30 mL of propylene glycol and 24 mL of ethanol, and the mixture was stirred for 1 h until it was uniformly mixed. The titanium sheet treated in step (b) and the mixed solution were transferred into a reactor and reacted at 180°C for 12 h, cooled naturally to room temperature, and then placed in a muffle furnace and heated to 350°C at a heating rate of 5°C / min and calcined for 1 h, and cooled naturally to room temperature. (d) Loading precious metal catalysts: The material prepared in step (c) is impregnated in a solution of chloroplatinic acid by an equal volume impregnation method and dried in an inert atmosphere. The photoanode finally obtained is 3wt.% Pt / titanic bismuth acid / titanium oxide / titanium; (2) Preparation of alcohol ether carboxylates by electrochemical modification: 3wt.% Pt / titanic bismuth acid / titanium oxide / titanium photoanode and platinum cathode are respectively inserted into an electrolytic cell solution, wherein the electrolyte solution is an emulsion composed of 15-20g fatty alcohol polyoxyethylene ether, 1-1.5g sodium chloride, and 500-750mL deionized water. A DC voltage is used with a voltage intensity of 20-30V, a xenon lamp is used as the light source, and the light intensity of the light is 15-30mW / cm 2 , temperature is 25-35°C, stirring speed is 150-200rpm, time is 10-12h; (3) Concentrate by vacuum distillation to obtain the modified surfactant.

Citation Information

Patent Citations

  • A kind of electrochemical synthesis method of fatty alcohol polyoxyethylene ether carboxylic acid or its salt

    CN105568310B